2015
DOI: 10.1175/mwr-d-14-00221.1
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Roles of Air–Sea Coupling on Different MJO Events: A New Perspective Revealed from the DYNAMO/CINDY Field Campaign*

Abstract: Previous observational analysis and modeling studies indicate that air–sea coupling plays an essential role in improving MJO simulations and extending MJO forecasting skills. However, whether the SST feedback plays an indispensable role for the existence of the MJO remains controversial, and the precise physical processes through which the SST feedback may lead to better MJO simulations and forecasts remain elusive. The DYNAMO/Cooperative Indian Ocean Experiment on Intraseasonal Variability in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 140 publications
5
59
0
Order By: Relevance
“…Convection in the Indian Ocean weakens in early December when the region of active convection is in the MC. The lack of the strong convection of MJO1 approximately on 6 November in the MC region is similar to the simulation initialized on 7 October of Fu et al (2015) and the earlier initiation of MJO2 by approximately 5 days is also common with their simulation initialized on 4 November. These defects are readily detectable in Fig.…”
Section: The Control Casesupporting
confidence: 68%
See 2 more Smart Citations
“…Convection in the Indian Ocean weakens in early December when the region of active convection is in the MC. The lack of the strong convection of MJO1 approximately on 6 November in the MC region is similar to the simulation initialized on 7 October of Fu et al (2015) and the earlier initiation of MJO2 by approximately 5 days is also common with their simulation initialized on 4 November. These defects are readily detectable in Fig.…”
Section: The Control Casesupporting
confidence: 68%
“…These defects are readily detectable in Fig. 3 of Fu et al (2015), although they did not point these explicitly. In contrast, the 76 day simulation of Wang et al (2015) appears to successfully reproduce the strong convection approximately on 6 November.…”
Section: The Control Casementioning
confidence: 93%
See 1 more Smart Citation
“…Modeling studies have also been undertaken with operational forecasts Fu et al 2013;Ling et al 2014;Kerns and Chen 2014a) and global/regional model simulations (Fu et al 2015;Hannah and Maloney 2014;Miyakawa et al 2014;Nasuno 2013;Subramanian and Zhang 2014;Chen et al 2015;Hagos et al 2014a, b;Seo et al 2014;Wang et al 2015). With regard to the moistening process of the MJO, a special focus has been given on multi-scale processes (Chen et al 2015;Hagos et al 2014b;Kerns and Chen 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The significant impact of the diurnal sea surface temperature (SST) variation on moisture buildup prior to the active phase of the MJO was demonstrated; Chen et al (2015) addressed that the diurnal SST variation contributed to the moisture resurgence in the suppressed period of the MJO event through enhancement of moisture transport associated with the atmospheric mixed Rossby-gravity waves, and Seo et al (2014) reported the impacts of the collocation of the diurnal peaks of SST and latent heat fluxes. Fu et al (2013Fu et al ( , 2015, who evaluated the forecast skill of operational and research models, concluded that the air-sea coupling enabled a better prediction skill of MJO events.…”
Section: Introductionmentioning
confidence: 99%